ANALISIS FINANSIAL AGROINDUSTRI KERUPUK OPAK DI DESA BUKIT PENINJAUAN II KECAMATAN SUKARAJA KABUPATEN SELUMA - Sarina Sarina; Hermawati Hermawati; Chaidir Chaidir (University of Prof. Dr. Hazairin, SH, 2020)
ABSTRACT Business Analysis Of The Opak Agroindustry In Bukit Peninjaun Ii Village, Sukaraja District, Seluma Regency One sub-sector that is very important to be developed to support agricultural development is the agricultural product processing industry (agro-industry). The purpose of the study was to determine the amount of production, revenue, income, efficiency, BEP opak agro-industry costs in Bukit Peninjau II Village, Sukaraja District, Seluma Regency. The study was conducted in March to May 2017 in Bukit Peninjaun II Village, Sukaraja District, Seluma Regency. The method used is census method. The data used are primary and secondary data. Analysis of financial data used is the analysis of production costs, revenue and income analysis, R / C ratio analysis and break-even analysis (BEP). Research results show that the average production is 20 kg / production, the total production cost is Rp. 106,445.51 with an average selling price of Rp. 12,000, - / kg. The revenue is Rp. 240.00, - and income of Rp. 133,554.49. R / C ratio greater than 1 which is 2.25, means that the opak cracker agroindustry is profitable and efficient. Keywords: Business analysis, opak cracker